Gut Microbiota in Chronic Inflammatory Diseases - Literature Review - Zygadło, Joanna; Jałocha, Kamila; Bakuła, Piotr (Journal of Education, Health and Sport, 2025)
Introduction The gut microbiota, a complex community of microorganisms residing in the human gastrointestinal tract, is integral to various bodily functions. Understanding the role of gut microbiota is essential due to its significant influence on human health and disease. Current research indicates that gut microbiota can modulate immune responses and maintain homeostasis. Despite extensive studies, the specific mechanisms by which gut microbiota influences chronic inflammatory diseases remain unclear. Investigating the interaction between gut microbiota and the immune system can provide new insights into potential therapeutic strategies for chronic inflammatory diseases. Aim of the study This study aims to elucidate the mechanisms by which gut microbiota affects immune responses, particularly in chronic inflammatory conditions. We hypothesize that alterations in gut microbiota composition can significantly modulate immune responses, thereby influencing the progression of chronic inflammatory diseases. Conclusions We discuss potential therapeutic interventions targeting the gut microbiota for chronic inflammatory diseases that encompass several approaches. These include the administration of probiotics and prebiotics, fecal microbiota transplantation (FMT), diverse dietary modifications. Personalized microbiome-based therapies offer tailored interventions that combine various methodologies. Further scientific investigation is necessary to comprehensively elucidate and optimize these therapeutic strategies.